Degradação eletroquímica e fotoquímica em série do herbicida picloram utilizando um anodo dimensionalmente estável e luz UV - Coledam, Douglas Augusto Constantino (Universidade Federal de São Carlos, 2016)
A coupled electrochemical-photochemical system (EQ-FQ) using a dimensionally stable anode (ADE) and UV light was used for the oxidation and mineralization of picloram (PCL) herbicide, which is a potential contaminant of surface water and groundwater. The electrochemical process was conducted using a filter-press flow cell and the photochemical one through direct irradiation of the solution in the reservoir using a Hg lamp (UVA and UVC radiation). For the combined system (EQ-FQ), both processes were simultaneously used. In the first part of this work, the investigated variables were: i) type/nominal power of the Hg lamp (UVA 9 W and UVC 5 and 9 W) and ii) initial [Fe2+] (0.0; 0.5, 1.0 and 2.0 mmol L-1). In the second part, which was carried out using a 5 W UVC light, the investigated variables were: i) pH (3, 7, 11 and without control) and ii) [NaCl] (0, 1, 2 and 4 g L-1). Other parameters were kept constant such as, flow rate (420 L h-1), temperature (25 °C), current density (20 mA cm-2), [PCL] (100 mg L-1) and [Na2SO4] (0.1 mol L-1). In the optimized conditions of the second part (5 W UVC lamp, without pH control, and using NaCl 1,0 g L_1), a electrochemical treatment was carried out comparatively and using a boron-doped diamond anode (EQ-DDB). High performance liquid chromatography coupled to mass spectrometry and total organic carbon measurements were used to monitor the [PCL] and of its intermediates, as well as the degree of mineralization (CO2 conversion), respectively. The EQ-FQ system using a 9 W UVA light exhibited a synergistic effect during PCL mineralization in comparison to its oxidation. High CO2 conversion rates were attained when using an initial concentration of Fe2+ equal to 1,0 mmol L-1, due to the formation of HO* and Cl* radicals. This might be due to HOCl homolysis mediated by Fe2+ ions (Fenton like reaction). Nevertheless, experiments using a UVC light were more promising for the oxidation and mineralization of PCL. In the second part, acidic to neutral solutions, independently of the NaCl amount, led to high PCL oxidation and mineralization rates. That behavior is due to the chemical oxidation mediated by HO* and Cl* radicals, which were photogenerated by the HOCl homolysis. The EQ-FQ system showed comparable efficiencies, in some conditions superior, concerning the oxidation and mineralization of PCL, degree of conversion to CO2, and mineralization current efficiency in comparison to the EQ-DDB process. Few reaction byproducts were detected and only one of them resulting from hydroxylation reactions. This result indicates the attack of HO* radicals originating from the EQ-FQ process. Concerning short chain carboxylic acids, the EQ-FQ process produced dichloroacetic acid (and others), which was almost completely consumed during treatment; however, the EQ-DDB process produced small amounts of chloroacetic acid, which was not completely eliminated during treatment. Finally, the treated solution using the EQ-FQ process exhibited no toxicity towards Escherichia Coli bacteria.
Coupled electrochemical and photochemical degradation of picloram herbicide using a dimensionally stable anode and UV light
Keywords: Compostos orgânicos sintéticos; Anodo dimensionalmente estável; Herbicida Picloram (PCL); Radiação; Cromatografia líquida de alta eficiência; Espectrometria de massas; CIENCIAS EXATAS E DA TERRA::QUIMICA